2010
DOI: 10.1590/s0103-90162010000200009
|View full text |Cite
|
Sign up to set email alerts
|

Quality of sausage elaborated using minced Nile Tilapia submmitted to cold storage

Abstract: Filleting yield of Nile tilapia Oreochromis niloticus (L.) is low (30%) and generates large amount of wastes that may turn into environmental and economic problem. However, these wastes can be used for the extraction of minced fish (MF) which can be used in the preparation of sausages. The objective of this study was to assess the quality of sausages prepared with 0, 20, 40, 60, 80 and 100% of MF from Nile tilapia filleting waste during storage at 0±0.3ºC. Alterations in the instrumental color (L*, a* and b*),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 24 publications
2
21
1
5
Order By: Relevance
“…In a study in Turkey of cultured Oncorhynchus mykiss (Mashaii et al, 2012), the protein (17.4 -17.9%) and ash (1.38 -1.59%) contents were similar than our results, while the moisture (75.2 -76.9%) and total fat (2.48 -4.88%) contents were lower and higher, respectively. In general, the wet contents in the muscle fish of this study were within the range reported by Jabeen & Chaudhry (2011) and Campagnoli de Oliveira et al (2010). Fat content was affected by production systems and this variation in the total fat content was consistent with the conclusions of Gonzalez-Artola (2004) and Jabeen & Chaudhry (2011).…”
Section: Proximate Compositionsupporting
confidence: 91%
“…In a study in Turkey of cultured Oncorhynchus mykiss (Mashaii et al, 2012), the protein (17.4 -17.9%) and ash (1.38 -1.59%) contents were similar than our results, while the moisture (75.2 -76.9%) and total fat (2.48 -4.88%) contents were lower and higher, respectively. In general, the wet contents in the muscle fish of this study were within the range reported by Jabeen & Chaudhry (2011) and Campagnoli de Oliveira et al (2010). Fat content was affected by production systems and this variation in the total fat content was consistent with the conclusions of Gonzalez-Artola (2004) and Jabeen & Chaudhry (2011).…”
Section: Proximate Compositionsupporting
confidence: 91%
“…When comparing both treatments under the group that was vacuum-packaged, the decrease in pH values was higher in pasteurized sausages probably due to the lower efficiency of the pasteurization method in microbiological control when compared with smoking. The same pH reduction during storage was observed by Oliveira Filho et al (2010a) in sausages made of MSM from tilapia, with a pH of 6.48 on day 5 and a pH of 6.27 on day 40 of storage.…”
Section: Resultssupporting
confidence: 75%
“…Oliveira Filho et al (2010) did not detect pathogenic microorganisms (Staphylococcus aureus and Salmonella sp.) in a sausage based on minced Nile tilapia (O. niloticus) and total coliform population in the sausage evaluated by the Most Probable Number (MPN) method.…”
Section: Microbiological Analysesmentioning
confidence: 90%
“…Studying the quality and formulation of fresh sausage of Indian sardines (Sardinella longiceps), Ravishankar, Setty and Shetty (1992) found similar results, with 3.99 log CFU.g -1 mesophilic on day zero. In the same way, studying the microorganisms of fresh sausage of tilapia, (Oreochromis niloticus), Oliveira Filho et al (2010) observed psychrotrophs during storage, and the initial results were ≤ 2 log CFU g -1…”
Section: Evaluation Of Raw-materials Qualitymentioning
confidence: 91%